Process and parameter optimisation for micro structuring of 3D freeform metallic surfaces: A comparative study of short-pulse (nanosecond) and ultrafast (picosecond, femtosecond) laser ablation - Scholz, Steffen G. (2017)
Layer-based laser ablation of three dimensional micro structured freeform surfaces has become of significant importance for technical applications such as biomimetic surfaces in recent years. In order to identify the optimum set of process parameters for a complex laser ablation operation, a design of experiments (DoE) study has been carried out with laser sources covering pulse durations regime of femtosecond (fs), picosecond (ps) and nanosecond (ns). The aim was to identify the optimum parameter set for achieving best surface roughness and, as a second criteria, for machining time to be reduced to a minimum. In a first step, rectangular pockets have been machined and a DoE based parameter variation was performed. In particular, the parameters wavelength (1030 nm, 515 nm, 343 nm), machining speed, laser power, and laser pulse duration (fs, ps, ns) have been modified. Surface roughness and ablated depth were measured and an optimum set of parameters was calculated. The results show that the ultraviolet laser type (343nm) has the best performance to achieve lowest surface roughness and with a laser pulse duration of 3445 fs reaches also the best ablation efficiency in relation to machining time. While machining speed and laser power have an almost linear influence on achievable roughness, laser pulse duration has a quadratic influence in relation to a global minimum on the surface roughness result. For the ablated depth, machining speed and laser power have an almost linear influence while laser pulse duration has a quadratic influence in relation to a global maximum.